Analysis of the Key Success Factors in the Oil Market of China National Petroleum Corporation (PetroChina) - E Fan; Tatiana Samuseva (Communications of International Proceedings, 2021)
The oil refining industry plays a significant role in the development of the world fuel and energy complex. At the same time, it should be noted that at the present stage of the industry's development, qualitative changes are taking place in it. The key factors that will determine the development of global oil refining in the future: increasing demand for refined products in developing countries, deepening the integration of oil refining companies, concentration of small and medium-sized oil refineries in the production of innovative products. China's oil industry is represented by three main companies - PetroChina, CNOOC and SINOPEC. Based on the analysis of PetroChina, it can be concluded that the main factors of success in the Chinese market are strong government support and specialization in certain sectors of the industry. Thus, the article assesses the possibilities and long-term prospects for the development of PetroChina under the influence of modern trends in the development of the world economy and internal factors of the Chinese energy industry.
Keywords: Oil; Oil and Gas Industry; China; Chinese Economy; Oil Export; PetroChina.